PENGARUH MOTIVASI DAN PROFESIONALISME ASN TERHADAP EFEKTIVITAS KERJA DI LINGKUNGAN KANTOR KEMENTERIAN AGAMA KOTA PADANG - Eldison Eldison (Lembaga Administrasi Negara, 2018)
This study aims to know the implication of the existence of a positive or significant influence between motivation and ASN Professionalism. The method used is survey method by applying Grounded Research. The population in this study is all ASN in the office environment of the Ministry of Religious Affairs of Padang City with the number of 322 ASNs consisting of ASN in the offices of the Ministry of Religious Affairs of Padang City, Madarasah Aliyah as the city of Padang, Madrasah Tsanawiyah and the Office of Religious Affairs of Padang City. Sample in this research is counted 60 people with random sampling technique. Data Collection Technique uses questionnaire. The variables measured are independent variables, namely: Motivation (X1) and Professionalism (X2), while the dependent variable is Work Effectiveness (Y). Analysis of the influence of variables of Motivation and Professionalism of Apparatus, either jointly or independently to the Effectiveness of Ministry of Religious Affairs Office of Padang City showed significant results. This shows that the two independent variables, namely Motivation and Professionalism Apparatus either together or individually can improve the Effectiveness of ASN Work at the Office of the Ministry of Religious Affairs of Padang City. Thus the influence of these two independent variables on increasing Effectiveness of ASN Work at the Office of the Ministry of Religious Affairs of Padangisverymeaningful.Keywords: Motivation, ASN Professional, Work Effectiveness.